The role of dialogue leadership in enhancing organizational loyalty: An analytical study of the opinions of a sample of workers in the General Directorate of Education in Babylon (Entrepreneurship Journal for Finance and Business, 2025)
This research aims to show the effect of conversational leadership in enhancing organizational loyalty at the level of a sample of individuals working in the General Directorate of Education in Babylon. There are three organizational dimensions: emotional loyalty, moral loyalty, and continuous loyalty. The research started with a main problem that included many questions revolving around the nature of the relationship between its field variables, the most important of which was (What is the level of influence of dialogue leadership with its dimensions on organizational loyalty from the point of view of the research sample?) through the research sample, which included a sample of workers in the General Directorate of Education in Babylon The sample of the study was (84) individuals working in that directorate. The questionnaire was used as a main tool in collecting data and information needed for research. For the purpose of data analysis and statistical processing, the researcher relied on a set of statistical methods available in the two programs (SPSS V.24 and Amos V.23). , respect, comment, expression) and organizational loyalty in its dimensions (emotional, moral, continuous).In light of the conclusions, a set of recommendations were formulated, most notably enhancing the creative energy of others through expressing an opinion and using the method of brainstorming and creative thinking